Thulium laser vaporesection of the prostate: Can we operate without interrupting oral antiplatelet/anticoagulant therapy? - ŞENER, TARIK EMRE; TANIDIR, YILÖREN (KOREAN UROLOGICAL ASSOC, 2017)
Purpose: Thulium vaporesection of the prostate (ThuVARP) is a new and safe approach for patients receiving anticoagulant therapy in whom transurethral resection of the prostate (TURP) may possess a high bleeding risk. We aimed to demonstrate the efficacy and safety of ThuVARP in patients receiving oral antiplatelet/anticoagulant (OAP/OAC) therapy. Materials and Methods: A total of 103 patients who underwent ThuVARP between 2011 and 2013 were enrolled in the study. Patients were divided into 2 groups. Group A consisted of 47 patients who underwent low molecular weight heparin ( LMWH) bridging and group B consisted of 56 patients who were operated on while receiving OAP/OAC therapy. Results: The drop in hemoglobin levels in the pre- and postoperative periods was significantly higher in group A than in group B. When subgroups were analyzed, the mean drop in hemoglobin was significantly lower in the warfarin and ticlopidine subgroups of group B than in group A. International Prostate Symptom Scores were significantly lower 3, 12, 18, and 24 months after surgery in group A than in group B. Quality of life scores, maximal flow rate values, and postmicturition residual urine volumes (mL) were similar between the 2 groups. A total of 38 and 41 patients in groups A and B, respectively, had no complications. Conclusions: Our study showed the safety profile of continuing different OAP/OAC therapies in terms of bleeding problems in patients undergoing ThuVARP. We strongly recommend abandoning LMWH bridging and maintaining the OAP/OAC regimen patients are already receiving.
Keywords: Anticoagulants; Low-molecular-weight heparin; Thulium; Transurethral vaporesection of prostate; MOLECULAR-WEIGHT HEPARIN; TRANSURETHRAL RESECTION; COMPLICATIONS; OUTCOMES; SAFETY; ANTICOAGULANT; VAPORIZATION; HYPERPLASIA; OBSTRUCTION; ANTIPLATELET